The Meaning of Ujungan Tradition in Seren Taun Ceremony: A Phenomenological Study of Kasepuhan Cibadak Community - Sugiarta, Nugraha; Anggraeni, Risa; Reza, Faisal (Yayasan Sinergi Kawula Muda, 2024)
The Ujungan tradition is an attraction performed by a group of people, where participants whip each other using rattan. This tradition is held once a year during the Seren Taun traditional ceremony. The purpose of this study is to explore the experiences, motives, and meanings of the Ujungan tradition for its performers within the Kasepuhan Cibadak community, Lebak Regency, Banten. This study employs a qualitative method with Alfred Schutz’s phenomenological approach. Primary data collection techniques include active participant observation and semi-structured interviews, while secondary data are obtained from document studies/documentation. The study involves four key informants who are Ujungan performers and two supporting informants, consisting of spectators and cultural experts. Data validity is ensured through source triangulation. The findings reveal that the performers experience emotional enjoyment. The